Instilling Entrepreneurial Values at SMK Muhammadiyah 2 Karanganyar - Fajar, Ahmad Luhfi Septiyan; Budiyanto, Sapto Mei (Proceedings International Conference on Education Innovation and Social Science, 2023)
The purpose of instilling entrepreneurial values is to form individuals who have an entrepreneurial spirit. By emphasising entrepreneurial values such as innovation, creativity, healthy risk, perseverance, and courage, individuals are expected to develop a proactive, independent, and oriented attitude towards creating business opportunities. This research aims to find out how the cultivation of entrepreneurial values includes supporting factors and inhibiting factors in the cultivation of entrepreneurial values. This research uses qualitative methods with ethnographic design. The subjects of this research are entrepreneurship subject teachers and students of SMK Muhammadiyah 2 Karanganyar. The object of this research is the cultivation of entrepreneurial values at SMK Muhammadiyah 2 Karanganyar. Data collection techniques using observation, interviews, and documentation. The data validity technique used is source triagulation. Data analysis techniques by means of data reduction, data presentation, and conclusion drawing. The results showed that Penanman entrepreneurial values in schools is very important because to form individuals who have an entrepreneurial spirit. Through the cultivation of entrepreneurial values such as innovation, creativity, healthy risk, perseverance, and courage, individuals are expected to develop a proactive, independent, and orientated attitude towards creating business opportunities. The cultivation of entrepreneurial values aims to encourage student innovation and creation by thinking out-of-the-box, looking for new ideas and generating innovative ideas that can be applied in business. The cultivation of entrepreneurial values emphasises the values of discipline, responsibility, collaborative, creative and communicative values.